The Carcass Evaluation of Super Native chicken That Giving Tumeric Flour (Curcuma domestica Val.) - Dunggio, Alan; Datau, Fahria; Dako, Safriyanto; Handayani, Sayekti (AgriSains, 2021)
This study aims was to determine the effect of giving turmeric flour (Curcuma Domestica Val) in the rations on the percentage of super native chicken carcass.In this study, 80 super native chickens were placed in 20 cages with 4 chickens in each cage. The method used in this study was the completely randomized design method (CRD) with 4 treatments and 3 replications. The treatments used in this study were A (without turmeric flour or control), B (2% turmeric flour), C (4% turmeric flour), and D (6% turmeric flour). The variables observed were live weight, carcass weight, and carcass percentage. The results showed that the addition turmeric flour (Curcuma Domestica Val) had no significant effect on live weight, carcass weight, and carcass percentage of super native chicken. Giving turmeric flour to a level of 6% did not affect live weight, carcass weight, and carcass percentage.